2009 World Congress on Privacy, Security, Trust and the Management of E-Business 2009
DOI: 10.1109/congress.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Web Authentication Using Mikon Images

Abstract: Authentication is mostly achieved by means of the ubiquitous password. This is suboptimal in some settings, such as for user groups with cognitive or language difficulties. Many web-based systems have user groups with widely ranging capabilities, and more innovative authentication mechanisms should be investigated to enhance usability and accessibility while still delivering the required level of security to authorise legitimate users.This paper presents details of an authentication system which relies on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The idea is that humans can remember images better than recalling alphanumeric text [4,5] and so this may be a way of devising more memorable passwords. Given the need for alternative usable authentication systems and existing interest in image passwords [3,6,7,8,9,10] as a potential solution, we identify an important limitation of existing work: most prior studies with images as passwords, except [11,12], have focused on the usability of a single password. However, people will need to remember and use multiple image passwords in the same way that they currently use multiple alphanumeric passwords.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea is that humans can remember images better than recalling alphanumeric text [4,5] and so this may be a way of devising more memorable passwords. Given the need for alternative usable authentication systems and existing interest in image passwords [3,6,7,8,9,10] as a potential solution, we identify an important limitation of existing work: most prior studies with images as passwords, except [11,12], have focused on the usability of a single password. However, people will need to remember and use multiple image passwords in the same way that they currently use multiple alphanumeric passwords.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have reported the usability of faces [3,7], Mikons [6,10], doodles [6,9], abstract art [8] and pictures of daily objects [7]; however, these studies have focused only on the use of single passwords. We are aware of only two pieces of prior work that studied multiple image passwords: [12] studied the use of multiple facial passwords and [11] compared multiple picture passwords to that of multiple PIN's.…”
Section: Background Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These images have superior memorability because they have been provided by the users. As explained in [30], the actions engaged in during production of these images enhance memorability.…”
Section: Using Simple Image Types In Authenticationmentioning
confidence: 99%
“…Different image types have been trialled, with some demonstrating more efficacy than others: faces [10], abstract art [25], system provided or user-taken photographs [26,27], icons [28], doodles [29] and Mikons [30]. A comparison between photographs, user photographs and doodles showed that doodles performed best in terms of memorability [31].…”
Section: Using Simple Image Types In Authenticationmentioning
confidence: 99%